2016
DOI: 10.1080/09540105.2016.1148124
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of Aflatoxins in commercial pepper in Iran

Abstract: During the period from September to November 2014, occurrences of Aflatoxin B1, B2, G1, and G2 (AFB1, AFB2, AFG1, and AFG2) were determined in 76 pepper samples consisting black pepper (n = 40) and red pepper (n = 36) obtained from local markets of Isfahan province, Iran. Aflatoxins' (AFs') analyses were carried out by using the high-performance liquid chromatography (HPLC) method. AFB1 levels in 32 (88.9%) of 36 red pepper samples were higher than the Iranian and European maximum permitted level (>5 µg/kg). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…In a survey conducted in Iran, aflatoxin was detected in 5 of 40 black pepper samples (12.5%) in levels ranging from 0.88 to 1.45 µg/kg. In the same study,100% of 36 red pepper samples were contaminated with aflatoxin ranging from 4.22 to 28.6 µg/kg (Barani et al., 2016). In another survey conducted in India, aflatoxin was detected in 78.1% of 55 black pepper samples contaminated with total aflatoxins with average amount of 320 ppb (Jeswal & Kumar, 2015a).…”
Section: Agricultural Products and Foods Contaminated By Aflatoxinsmentioning
confidence: 94%
“…In a survey conducted in Iran, aflatoxin was detected in 5 of 40 black pepper samples (12.5%) in levels ranging from 0.88 to 1.45 µg/kg. In the same study,100% of 36 red pepper samples were contaminated with aflatoxin ranging from 4.22 to 28.6 µg/kg (Barani et al., 2016). In another survey conducted in India, aflatoxin was detected in 78.1% of 55 black pepper samples contaminated with total aflatoxins with average amount of 320 ppb (Jeswal & Kumar, 2015a).…”
Section: Agricultural Products and Foods Contaminated By Aflatoxinsmentioning
confidence: 94%
“…AFB1 maximum limit for spices in Iran, Korea and Japan are respectively; 5, 10 and 10 µg/kg (FAO, 2003). In the study conducted in Iran according to Table 1, AFB1 was detected in 100% of the red pepper spice samples with an average concentration of 15.51 µg/kg (Barani et al, 2016). In the study conducted in Japan, AFB1 in red pepper spice was found at an average concentration of 0.17 µg/kg (Sugita-Konishi et al, 2010).…”
Section: Aflatoxin B1 Concentrationmentioning
confidence: 95%
“…In studies where such mean can be calculated, means and standard deviations are calculated and used (Colak et al, 2006;Cavus et al, 2018). The studies at which the mean and standard deviation were not given or calculated were not used in calculating the mean concentration (Barani et al, 2016;Ozturk, 2017;Sugita-Konishi et al, 2010;Tosun & Arslan, 2013). When these results are added, the average AFB1 content is calculated as 6.61 (µg/kg).…”
Section: Aflatoxin B1 Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromatographic separation was performed on a Discovery C18 HPLC column (5 µm particle size, 250 mm× 4.6 mm) protected with a Discovery C18 Supelguard column (5 µm particle size, 20 mm× 4.6 mm). The post-column derivatization of AFs was carried out by using a Kobra cell electrochemical bromine system [10]. About 25 ±0.10 g of tested sample with addition of 70:30 methanol: water extraction solvents were mixed into the flask of 250 mL.…”
Section: Determination Of Aflatoxinmentioning
confidence: 99%